Knowledge, attitude and practices regarding cervical and breast cancer: a comparative study in a tertiary care centre - Chaurasia, Amrita; Upadhyay, Anupma; Kumari, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical and breast cancer are commonest cancer among Indian females. Timely screening through simple methods can prevent advanced stage of disease, thereby preventing mortality. Updated knowledge about available standard preventive methods have a huge impact in improving the acceptance and thus increasing the percentage of screened, vaccinated and treated population. Objective were to evaluate and compare knowledge, attitude and practices about cervical and breast cancer among paramedics and hospital visitors at tertiary care teaching institute. Methods: 100 participants; 50 each of paramedics and hospital visitors of Swaroop Rani hospital Prayagraj were assessed for knowledge, attitude and practices regarding cervical and breast cancer using predesigned questionnaire. Results: The 100% of paramedics had heard about cervical and breast cancer while among hospital visitors only 66% had heard about cervical cancer and 78% about breast cancer. Regarding in depth knowledge of symptomatology paramedics had higher percentage for both cervical and breast cancer. The knowledge of cervical and breast cancer screening methods was significantly higher among paramedics as compared to hospital visitors. Positive attitude regarding cervical and breast cancer was 60% and 74% among paramedics while 26% and 16% among hospital visitors. Both groups showed poor practice (34%,42% among paramedics while 12% and 6% in hospital visitors). Conclusions: Despite various focused programs on cancer awareness and preventive strategies being run already significant differences were observed in knowledge, attitude and practice of paramedics and hospital visitors. Although the knowledge was good among paramedic’s gap was seen in attitude and practice that warrants the need of focusing on awareness generation through different platforms.